Vibrational dynamics of solid molecular nitrogen to megabar pressures: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Goncharov, A. F.; Gregoryanz, E.; Mao, H.-K.; Hemley, R. J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We report the results of Raman and synchrotron infrared absorption measurements of severalmolecular phases of solid nitrogen to pressures above 100 GPa (300 K). Low-temperature vibrational spectra to 45 GPa are also presented. The changes in Raman and infrared spectra at 60 GPa and 300 K are interpreted as arising from the e→ z transition reported at low temperature. The character of splitting of the Raman vibron n2 observed at 25 GPa and low temperatures differs from that previously reported, a difference that we ascribe to different experimental procedures employed and metastability of the low-temperature phase.